Bioinspired Mononuclear Transition-Metal Aminopyridine Complexes for Olefin Epoxidation and Molecular Oxygen Activation: Synthesis, Characterization, Catalysis and Mechanistic Studies - Yang, Guang. (2017)
Abstract: ABSTRACT This thesis is aimed at developing selective oxidations with environmentally friendly oxidants derived from dioxygen, using biologically relevant 3d-transition metal complexes as catalysts. Specifically, selective olefin epoxidation with hydrogen peroxide and dioxygen activation reactions promoted by mono- and dinuclear transition-metal aminopyridine complexes of manganese (II) and iron (II) are described. Synthesis and characterization of related copper (II) complexes is also reported. The first part of this thesis focuses on hydrogen peroxide activation with manganese (II) and iron (II) complexes with 1,1′-bis[(pyridine-2-yl)methyl]-2,2′-bipiperidyl (PYBP) ligand, a newly designed tetradentate aminopyridine ligand with rigid diamine framework. The two symmetrical chiral centers of the PYBP distinguish the ligand and the complexes a pair of racemic and one meso isomers. The complexes are shown to act as efficient catalysts for selective olefin epoxidation using hydrogen peroxide as "green" oxidant. Catalytic and mechanistic studies of manganese complexes are presented in Chapter 1; the racemic complex converts olefin with up to 100% epoxide yield and 200 TON, while the meso complex presents no catalytic activity under all experimented conditions attempted in our study. The mechanisms of hydrogen peroxide activation and the origins of this "diastereoisomer effect" were investigated by stopped-flow kinetics and freeze-quench EPR techniques, coupled with electrochemistry, single crystal X-Ray crystallography, and computational chemistry. Chapter 2 presents analogous catalytic and mechanistic studies of the iron complexes, in comparison with those of the manganese complexes. Both iron (II) and manganese (II) complexes catalyze epoxidation reactions through a MV/MIII cycle, in which the oxometal (V) species are proposed as the active intermediates responsible for the oxygen atom transfer. Preliminary attempts to synthesize and characterize optically active catalysts are also included in the Chapter 2. Chapter 3 discusses dioxygen binding to a manganese (II) aminopyridine-thiolate complex, [MnII(SMe2N4-6-OMe-DPEN)]2(BPh4)2. This project is in collaboration with Prof. Julie Kovacs (University of Washington). The presence of covalently appended thiolate donor, as well as incorporation of electron donating substituents into the ligand, activates Mn(II) and increases its reactivity with O2. The reaction, which ultimately forms a μ-oxo dimanganese (III) product, proceeds through a series of intermediates, which rapidly form and decay at low temperatures. In addition to previously discovered by Kovacs and coworkers Mn(III) superoxo species [MnIII(SMe2N4-6-MeO-DPEN)(O2)]∙+, and dimanganese(III) peroxo species [MnIII(SMe2N4-6-MeO-DPEN)]2(trans-μ-1,2-O2)2+, several new species were observed in our work by stopped-flow spectrophotometry at low temperatures (-80~-44 °C), and assigned as [MnIII(SMe2N4-6-MeO-DPEN)]2(µ-η2:η2-O2)2+, [MnIV(SMe2N4-6-MeO-DPEN)]2(μ-O)22+ and [MnIV(SMe2N4-6-MeO-DPEN)](μ-O)(μ-OH)[MnIII(SMe2N4-6-MeO-DPEN)]2+ intermediates. The reaction rate constants calculated from single-wavelength and global fitting of the kinetic data are discussed and compared with those previously reported for less electron-rich [MnII(SMe2N4-6-Me-DPEN)](BPh4)2 complex (J. Am. Chem. Soc. 2013, 135 (15), 5631-5640). The synthesis, characterization and crystallographic studies of organic precursors and transition-metal complexes related to linear and macrocycle aminopyridine ligands are presented in Chapters 4 - 7. The topology and structural features of the compounds, including bond lengths, coordination geometry and supramolecular features, are highlighted. Chapter 8 summarizes all the achievements for the projects discussed in the previous chapters, and briefly introduces the future directions.; Thesis (Ph.D.)--Tufts University, 2017.; Submitted to the Dept. of Chemistry.; Advisor: Elena Rybak-Akimova.; Committee: Clay Bennett, and Arthur Utz.; Keyword: Chemistry.